P858 Impact of ileocaecal resection on gut microbiota in ileal Crohn's disease patients. (25th January 2019) - Opstelten, J; Paganelli, F; Bonten, M; Willems, R; Witteman, B; Leavis, H; Oldenburg, B
Abstract: Background: Ileocaecal resection is the most commonly performed operation for Crohn's disease (CD), but it is presently unclear if this affects the gut microbiome. This study aims to compare the gut microbiota composition between CD patients with and without an ileocaecal resection. Methods: Stool samples and clinical data were collected from 30 patients with ileal CD in remission with a history of ileocaecal resection and without previous bowel surgery (control group), matched for gender and age. The faecal microbiota composition was characterised by 16S ribosomal RNA sequencing. Microbial diversity was assessed using the Shannon index and principal component analysis. Taxonomic differences between the two groups were determined using the statistical framework analysis of composition of microbiomes (ANCOM). Results: In total, 15 patients with and 15 patients without a previous ileocaecal resection were included. The median time between surgery and study enrolment was 12 years. Gut microbial diversity was significantly reduced in patients who underwent an ileocaecal resection compared with the control group. This was accompanied by an increased relative abundance of the family Veillonellaceae and a decreased relative abundance of the family Ruminococcaceae and the genus Faecalibacterium in patients with a history of an ileocaecal resection. Conclusions: Gut microbial diversity is decreased in ileal CD patients who previously underwent an ileocaecal resection relative to ileal CD patients without a history of intestinal resection. This is associated with differences in the proportion of several bacterial taxa and suggests that ileocaecal resection has a profound impact on the gut microbiota in patients with CD.